(untitled) (Third Sector Social Economic Review, 2024)
Personality encompasses the whole of the characteristics that distinguish an individual from others. Theories related to personality have examined the factors that contribute to these differences, as well as the extent to which they influence the emergence and development of personality. Personality theories suggest that the period in which individuals are born and live can play a determining role in shaping their personality. Factors such as political, social, economic structure, and technological advancements of a particular era can lead individuals of that period to possess similar personality traits. In order for a group of people to be called a generation, they must be born approximately in the same years, share the conditions of the same age, therefore similar troubles and destinies, and be obliged to similar duties. Each generation’s personality traits lead to distinct expectations and work values in the business life. This study aims to explore the relationship between the personality traits and work values of Generation Z individuals who have recently entered the labourmarket. The ""Big Five Personality Scale"" was used to assess personality traits, and the ""Work Values Scale"" was used to measure work values. The research focused on teachers, who are among the professionals with the greatest impact on the upbringing of future generations. A survey was conducted with 276 Generation Z teachers in Gümüşhane province, and the data obtained was analyzed with the SPSS 22.0 program. Data were analyzed using correlation and linear regression analysis and frequency analysis. The study found a significant relationship between the personality traits and work values of Generation Z teachers.